Establishing Babesia bovis-Free Tick Colony Following Treatment of the Host with Diminazene Aceturate (Berenil) - Sharon Tirosh-Levy; Asael Roth; Binyamin Leibovich; Ludmila Fleiderovitz; Ohad Frid; Daniel Yasur-Landau; Ricardo Wolkomirskyi; Monica L. Mazuz (Pathogens, 2021)
Babesia bovis is a widely-spread tick-borne hemoparasite of cattle with major economic and animal welfare consequences. Rhipicephalus (Boophilus) annulatus is a one-host tick which transmits bovine babesiosis in the Middle East and Africa. Laboratory rearing of ixodid ticks is essential for the investigation on ticks or tick-borne diseases. Establishing a tick colony in the laboratory usually originates from ticks harvested in the field, which may be naturally infected with various pathogens. This especially applies to carriage of B. bovis as it is highly prevalent in endemic areas and is transmitted transovarially in ticks. Here, we describe the use of diminazene aceturate (Berenil) in order to establish laboratory colonies of Babesia-free R. annulatus, from ticks collected in the field. Ticks collected in the field were kept until oviposition and hatched larvae were introduced to naïve calves, which led to infection of the calves with B. bovis. Calves were then treated with diminazene aceturate several times until the engorged ticks dropped. The eggs and larvae collected from these ticks were parasite-free, as demonstrated both by infection of splenectomized calves and by PCR. This suggested protocol is a useful tool to create parasite-free tick colony and may, theoretically, also be beneficial to reduce parasite circulation in the field, although not recommended, as resistance to diamenizene aceturate might develop.